Central nociceptin/orphanin FQ system elevates food consumption by both increasing energy intake and reducing aversive responsiveness - Olszewski, Pawel K. (American Physiological Society, 2010)
Nociceptin/orphanin FQ (N/OFQ), the nociceptin opioid peptide (NOP) receptor ligand, increases feeding when injected centrally. Initial data suggest that N/OFQ blocks the development of a conditioned taste aversion (CTA). The current project further characterized the involvement of N/OFQ in the regulation of hunger vs. aversive responses in rats by employing behavioral, immunohistochemical, and real-time PCR methodology. We determined that the same low dose of the NOP antagonist [Nphe(1)]N/OFQ(1-13)NH(2) delivered via the lateral ventricle diminishes both N/OFQ- and deprivation-induced feeding. This anorexigenic effect did not stem from aversive consequences, as the antagonist did not cause the development of a CTA. When [Nphe(1)]N/OFQ(1-13)NH(2) was administered with LiCl, it moderately delayed extinction of the LiCl-induced CTA. Injection of LiCl + antagonist compared with LiCl alone generated an increase in c-Fos immunoreactivity in the central nucleus of the amygdala. The antagonist alone elevated Fos immunoreactivity in the paraventricular nucleus of the hypothalamus, nucleus of the solitary tract, and central nucleus of the amygdala. Hypothalamic NOP mRNA levels were decreased during energy intake restriction induced by aversion, as well as in non-CTA rats food-restricted to match CTA-reduced consumption. Brain stem NOP was upregulated only in aversion. Prepro-N/OFQ mRNA showed a trend toward upregulation in restricted rats (P = 0.068). We conclude that the N/OFQ system promotes feeding by affecting the need to replenish lacking calories and by reducing aversive responsiveness. It may belong to mechanisms that shift a balance between the drive to ingest energy and avoidance of potentially tainted food.